HEMODYNAMIC CHANGES IN PATIENTS WITH FIBROUS ALVEOLITIS - Shodikulova Gulandom Zikriyayevna; Najmiddinov Alisher Shavkatovich; Mansurov Dilmurod Norimovich (Journals Park Publishing, 2022)
Fibrosing alveolitis is a pathological process based on extensive lesion of interstitial lung tissue, leading to the development of fibrous changes and respiratory failure. The progression of fibrosing alveolitis is accompanied by a steady increase in weakness, weight loss, shortness of breath, unproductive cough, chest pain, cyanosis. Diagnostics is based on the data of radiography and computed tomography of the lungs, spirometry, lung biopsy. Treatment of fibrosing alveolitis includes anti-inflammatory and immunosuppressive therapy, oxygen therapy; according to the indications – lung transplantation.Fibrosing alveolitis is a relatively rare disease of unclear etiology, but it tends to increase. Fibrosing alveolitis more often affects men over 50 years of age (20 cases out of 100 thousand) than women (13 cases out of 100 thousand). Mortality in fibrosing alveolitis reaches 3.3 cases per 100 thousand populations.Interstitial lung diseases (ILD) are mainly chronic diseases of the lung tissue, manifested by inflammation and disruption of the structure of the alveolar walls, endothelium of the pulmonary capillaries, perivasal and perilymphatic tissues. A characteristic symptom of interstitial lung diseases is shortness of breath, which is a reflection of pulmonary insufficiency. In patients with combined pathology, there was a tendency of aggravation of desaturation and fibrosis on the processes of myocardial remodeling, on the occurrence of arrhythmias and progression of arterial hypertension (AH), coronary heart disease (CHD), leading to to aggravate circulatory insufficiency and respiratory insufficiency (1-3). There is evidence of the influence of oxidative stress (4,5), systemic inflammation, endothelial dysfunction (6,7) on the progression of cardiac diseases in fibrosing alveolitis. However, some features of the course of this comorbid pathology remain unspecified. It is also interesting to develop algorithms for the diagnosis and treatment of patients with these combined diseases, which determines the relevance of studying this problem.
Keywords: fibrosing alveolitis; diseases; arterial hypertension